Gram-negative enteric rods/Pseudomonas colonization in mucositis and peri-implantitis of implants restored with cemented and screwed reconstructions: A cross-sectional study. (2019)
To evaluate the association between Gram-negative enteric rods and Pseudomonas with mucositis and peri-implantitis, in implants restored with cemented and screw-retained reconstructions.